Reversal of maladaptive fibrosis and compromised ventricular function in the pressure overloaded heart by a caveolin-1 surrogate peptide - Pleasant-Jenkins, Dorea (Lab Invest, 2017)
Chronic ventricular pressure overload (PO) results in congestive heart failure (CHF) in which myocardial fibrosis develops in concert with ventricular dysfunction. Caveolin-1 is important in fibrosis in various tissues due to its decreased expression in fibroblasts and monocytes. The profibrotic effects of low caveolin-1 can be blocked with the caveolin-1 scaffolding domain peptide (CSD, a caveolin-1 surrogate) using both mouse models and human cells. We have studied the beneficial effects of CSD on mice in which PO was induced by trans-aortic constriction (TAC). Beneficial effects observed in TAC mice receiving CSD injections daily included: improved ventricular function (increased ejection fraction, stroke volume, and cardiac output; reduced wall thickness); decreased collagen I, collagen chaperone HSP47, fibronectin, and CTGF levels; decreased activation of non-receptor tyrosine kinases Pyk2 and Src; and decreased activation of eNOS. To determine the source of cells that contribute to fibrosis in CHF, flow cytometric studies were performed that suggested that myofibroblasts in the heart are in large part bone marrow-derived. Two CD45+ cell populations were observed. One (Zone 1) contained CD45+/HSP47 −/macrophage marker+ cells (macrophages). The second (Zone 2) contained CD45(moderate)/HSP47+/macrophage marker − cells often defined as fibrocytes. TAC increased the number of cells in Zones 1 and 2 and the level of HSP47 in Zone 2. These studies are a first step in elucidating the mechanism of action of CSD in heart fibrosis and promoting the development of CSD as a novel treatment to reduce fibrosis and improve ventricular function in CHF patients.